2020
DOI: 10.1186/s12911-020-01297-6
|View full text |Cite
|
Sign up to set email alerts
|

Combining structured and unstructured data for predictive models: a deep learning approach

Abstract: Background The broad adoption of electronic health records (EHRs) provides great opportunities to conduct health care research and solve various clinical problems in medicine. With recent advances and success, methods based on machine learning and deep learning have become increasingly popular in medical informatics. However, while many research studies utilize temporal structured data on predictive modeling, they typically neglect potentially valuable information in unstructured clinical notes. Integrating he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(95 citation statements)
references
References 22 publications
3
92
0
Order By: Relevance
“…In health care, DL models have also been used for predicting disease onset, prognosis, and health outcomes. [8][9][10] For example, Rajkomar and colleagues (2018) demonstrated that the long short-term memory (LSTM) DL algorithm was superior to traditional non-DL predictive models for predicting health-care outcomes in the general inpatient population. 11 In the area of HF, LSTM has been utilized to predict disease onset with promising performance.…”
Section: Introductionmentioning
confidence: 99%
“…In health care, DL models have also been used for predicting disease onset, prognosis, and health outcomes. [8][9][10] For example, Rajkomar and colleagues (2018) demonstrated that the long short-term memory (LSTM) DL algorithm was superior to traditional non-DL predictive models for predicting health-care outcomes in the general inpatient population. 11 In the area of HF, LSTM has been utilized to predict disease onset with promising performance.…”
Section: Introductionmentioning
confidence: 99%
“…Davoodi et al [29] and Hoogendoorn et al [24] predicted after 24 h and within a median of 72 h, respectively. Studies by Tang et al [33], Caicedo-Torres et al [36], Sha et al [38], and Zhang et al [41] predicted in-hospital mortality irrespective of the admission or discharge time.…”
Section: Mortality Predictionmentioning
confidence: 96%
“…In addition to the most commonly used data elements, other clinical information such as medications, intake/output variables, risk scores, and comorbidities were also utilized. Weissman et al [31] and Zhang et al [41] used clinical variables from both structured and unstructured data types for mortality prediction.…”
Section: Mortality Predictionmentioning
confidence: 99%
“…Data from the general population and subpopulations are yet to be effectively integrated with algorithms that contribute to a hybrid model of care as part of a general guide [5]. Machine learning and deep learning have until recently only been fed structured data in medical informatics, neglecting invaluable information from unstructured clinical notes [52]. Unstructured data from medical records combined with deep learning tools hold promise in identifying the most suitable candidates for a study on youth depression, but a reliable recommendation system has not been established [53].…”
Section: Digital Mental Health Implementation In a Hybrid Model Of Carementioning
confidence: 99%